Networked Authoritarianism and the Geopolitics of Information: Understanding Russian Internet Policy - Nathalie Maréchal (Media and Communication, 2017)
In the aftermath of the 2016 U.S. election, researchers, policymakers and the general public are grappling with the notion that the 45th president of the United States may very well owe his electoral victory to a sophisticated propaganda effort masterminded by the Kremlin. This article synthesizes existing research on Russia’s domestic information controls, its internet policy at the global level (notably via internet governance processes), and the country’s resurgence as a major geopolitical player to argue that policymakers as well as the general public should consider these themes holistically, particularly as they formulate responses to what many see as the Russian threat to Western liberal democracy. Russia may have lost the Cold War, but it is now waging information warfare against the liberal democracies of Europe and North America in a sophisticated bid to win the next round. Russia does not view internet governance, cybersecurity, and media policy as separate domains. Rather, all the areas covered by those disciplines fall under “information security” for Russian foreign policy. The paper begins by tracing the history of information controls within what is now the Russian Federation before discussing the role of information and internet policy in Russian foreign policy, drawing connections between the Russian government’s control and manipulation of information—including its internet policy—in the domestic and international arenas. Next, it discusses the spread of networked authoritarianism and suggests that a “geopolitics of information” will become increasingly necessary in the coming years. Just as networked authoritarianism establishes strategic infrastructures to control the message domestically and intervene in global media systems, liberal democracies need to rethink media and communication infrastructures to ensure they foster pluralist, rights-respecting societies that are resilient to authoritarianism and extremism. In doing so, they should resist the temptation to respond to this threat in ways that will erode democracy even further, such as expanded surveillance and limits on free expression.